1992
DOI: 10.1128/iai.60.7.2880-2886.1992
|View full text |Cite
|
Sign up to set email alerts
|

Spleen cell cytokine secretion in Mycobacterium bovis BCG-infected mice

Abstract: Three susceptible mouse strains, i.e., BALB/c (H-2d), C57BL/6 (H-2b), and major histocompatibility complex-congenic BALB.B10 (H-2b), were infected intravenously with 4 x 10(6) CFU of live Mycobacterium bovis BCG and analyzed 4 weeks later for in vitro spleen cell cytokine secretion in response to purified protein derivative (PPD), BCG culture filtrate (CF), BCG cellular extract, total BCG, the purified extracellular 30-32-kDa antigen (the fibronectin-binding antigen 85), or the intracellular 65-kDa heat shock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
1

Year Published

1993
1993
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(65 citation statements)
references
References 33 publications
4
60
1
Order By: Relevance
“…Protective immunity against mycobacterial infection is primarily mediated by a cellular immune response of the Th1 type [41,49,[53][54][55]. IL-18, produced mainly by macrophages, plays a critical role in induction of cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Protective immunity against mycobacterial infection is primarily mediated by a cellular immune response of the Th1 type [41,49,[53][54][55]. IL-18, produced mainly by macrophages, plays a critical role in induction of cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, different species and even different breeds of the same species can develop diverse immune responses after vaccination with the same antigens. For example, it has been reported that mice of H-2 b and H2 d haplotype can develop Th1and Th2-type responses, respectively, after BCG vaccination [34,35]. Secondly, the balance between cellular and humoral immune responses induced following vaccination or infection could also be influenced by the nature of the antigens.…”
Section: Discussionmentioning
confidence: 99%
“…The T cell subset induced by mycobacterial infections may be influenced by the H-2 haplotype of the mice. A study by Huygen et al [199] examined cytokine production in vitro from spleen cells isolated from mice infected with BCG and while C57bl/6j mice (H-2B) mount a Th1 response, strains of the H-2D haplotype were found to be characterized by a substantial Th2 activation. The specificity of T cells generated at the height of infection is broad; a range of different culture filtrate antigens induce powerful proliferative responses and peak responses were reported to proteins in the region around 30 kDa and to small molecules below 12 kDa [22,200].…”
Section: An Integrated Model Of Cellular Dynamics and Antigen Recognimentioning
confidence: 99%